Introducing to the first issue - Acleto, Cesar (1974)
The presentation of the first issue of the REVISTA PERUANA DE BIOLOGíA, as official organ of dissemination of ASOCIACION DE BIOLOGOS DE LA UNIVERSIDAD DE SAN MARCOS, the reverse of the COVER is included with editorial information and BACK COVER with guidelines for authors and the reverse table with the CONTENS.